PENGARUH REPUTASI, ETIKA DAN PERSEPSI KEADILAN TERHADAP KESENJANGAN ANGGARAN (BUDGETARY SLACK) - Ernie Riswandari (Jurnal Akuntansi Bisnis, 2017)
Budgeting  carries  behavioral  problem  that  can have important effects on the effectiveness  of  organization.  Behavioral  problems  arise  when subordinates perceive that budgets are too difficult to accomplish so that subordinates often create slack in their budgets when superiors use budgets to evaluate performance. The research uses experimental design. This study tests the effect on budgetary slack of three potential control for opportunistic self-interest : reputation, ethics and perception of justice. In this setting, participants are divided to two groups based asymmetry and symmetry information.  The result shows that budgetary slack is negatively associated with reputation, ethic and perception of justice. Budgetary slack is positively associated with asymmetry information. Reputation, ethics and perception of justice are positively associated with social norms for honesty and responsibility. The result suggests that reputation, ethic and perception of justice affect to create slack in budgeting and can be used as control to minimize budgetary slack. Keywords: Budgetary slack, reputation, ethic, perception of justice, asymmetry                  information